Comic democracies from ancient Athens to the American republic - Fletcher, Angus, 1976- (Johns Hopkins University Press, 2016)
After recovering these lost chapters of our democratic past, Comic Democracies concludes with a draft for the future, using the old methods of comedy to envision a modern democracy rooted in the diversity, ingenuity, and power of popular art.